Placental Growth Factor Influences Maternal Cardiovascular Adaptation to Pregnancy in Mice - Aasa, Kristiina L. (Biol Reprod, 2014)
In healthy human pregnancies, placental growth factor (PGF) concentrations rise in maternal plasma during early gestation, peak over weeks 26–30, then decline. Since PGF in non-gravid subjects participates in protection against and recovery from cardiac pathologies, we asked if PGF contributes to pregnancy-induced maternal cardiovascular adaptations. Cardiovascular function and structure were evaluated in virgin, pregnant and postpartum C56BL/6-Pgf(−/−) (Pgf(−/−)) and C57BL/6-Pgf(+/+) (B6) mice using plethysmography, ultrasound, qPCR and cardiac and renal histology. Pgf(−/−) females had higher systolic blood pressure in early and late pregnancy but an extended, abnormal midpregnancy interval of depressed systolic pressure. Pgf(−/−) cardiac output was lower than gestation day (gd)-matched B6 after mid-pregnancy. While Pgf(−/−) left ventricular mass was greater than B6, only B6 showed the expected gestational gain in left ventricular mass. Expression of vasoactive genes in the left ventricle differed at gd8 with elevated Nos expression in Pgf(−/−) but not at gd14. By gd16, Pgf(−/−) kidneys were hypertrophic and had glomerular pathology. This study documents for the first time that PGF is associated with the systemic maternal cardiovascular adaptations to pregnancy.